Principles of macroeconomics - Ray C. Fair
The Scope and Method of Economics.- The Economic Problem: Scarcity and Choice.- Demand, Supply, and Market Equilibrium.- Demand and Supply Applications.- Concepts and Problems in Macroeconomics.- Inroduction to Macroeconomics.- Measuring National Output and National Income.- Unemployment, Inflation, and Long-Run Growth.- The Core of Macroeconomic Theory.- Aggregate Expenditure and Equilibrium Output.- The Government and Fiscal Policy.- Money, the Federal Reserve, and the Interest Rate.- The Determination of Aggregate Output, the Price Level, and the Interest Rate.- Further Macroeconomic Issues.- Policy Effects and Cost Shocks in the AS/AD Model.- The Labor Market in the Macroeconomy.- Financial Crises, Stabilization, and Deficits.- Household and Firm Behavior in Macroeconomy: A Further Look.- Long-Run Growth.- Alternative Views in Macroeconomics.- The World Economy.- International Trade, Comparative Advantage, and Protectionism.- Open-Economy Macroeconomics: The Balance of Payments and Exchange Rates.- Economic Growth in Developing Countries.- Methodology.- Critical Thinking about Research.